Quantum-chemistry calculation of BnNn-rings (n = 1-6) and fulborenes, the fullerene-like molecules BnNn (n = 12, 24, 60) - Sheichenko, D.M.; Pokropivny, A.V.; Pokropivny, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Electronic structure of the boron nitride rings and fullerene-like BN-molecules (the fulborenes) are calculated using MNDO, AM1, Extended Huckel, INDO and ab initio (STO-3G) methods. The fulborene B⁶⁰N⁶⁰ is confirmed as the boron nitride analogue of buckminster-fullerene C⁶⁰. Comparisons with other calculations are presented and possible applications as nanoporous materials and photonic crystals are discussed.